(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The provision of accessible and comprehensive banking products and services plays a pivotal role in promoting financial literacy and inclusivity. In this context, understanding the awareness and usage patterns of the public regarding these offerings is critical for the sustainable growth of the financial sector and the overall economic development of the region.